FEASIBILITY ANALYSIS OF ESTABLISHING A SHOWER GEL MANUFACTURING FACILITY IN KETAPANG, SOUTH LAMPUNG - Suryaneta, Suryaneta; Arianti, Annisa Rahma; Muhtar, Wafiq Azizah; Rahmadini, Sabili; Noviantoro, Tri (Indonesian Journal of Cosmetics, 2024)
The cosmetics industry has been experiencing rapid growth, driven by increasing consumer awareness of personal hygiene and self-care. Among personal care products, shower gels have gained significant market traction due to their convenience and perceived hygiene benefits compared to conventional bar soaps. This study evaluates the feasibility of establishing a shower gel manufacturing facility in Ketapang, South Lampung, by assessing key factors such as market potential, technical viability, financial sustainability, and regulatory compliance. The global shower gel market is projected to expand at a Compound Annual Growth Rate (CAGR) of 5.47%, reaching an estimated value of USD 70.88 billion by 2031. This trend is reflected in Indonesia, where demand for liquid personal care products has been steadily rising due to shifts in consumer lifestyles and increased disposable incomes. Despite the promising market outlook, the domestic cosmetics manufacturing sector faces challenges such as dependence on imported raw materials, supply chain inefficiencies, and limited local production capacity. This study examines whether localizing production in Ketapang, a region with access to natural resources and supportive industrial policies, can offer a competitive advantage. The research employs a feasibility study framework incorporating market analysis, technical assessment, financial modeling, and non-technical considerations. The financial analysis reveals that with an estimated production of 5,000 units per month, the facility is projected to generate IDR 523.2 million in revenue. The calculated cost of goods sold (HPP) per unit is IDR 87,204.86, with a selling price set at IDR 104,645.83 to maintain a 20% profit margin. Break-even analysis indicates that the facility must achieve a monthly sales volume of at least 7,500 units to cover all costs. The return on investment (ROI) is projected at 10.12%, with an estimated payback period of 9.88 years. The study also highlights regulatory requirements, including compliance with BPOM (Indonesian Food and Drug Authority) standards, Good Manufacturing Practices (GMP), and environmental sustainability protocols. Findings suggest that while the venture is financially and operationally viable, achieving profitability requires strategic interventions. These include securing local raw materials to reduce cost dependencies, optimizing production processes, implementing marketing strategies to increase brand competitiveness, and engaging policymakers for potential fiscal incentives. Overall, the establishment of a shower gel manufacturing facility in Ketapang presents a strong opportunity to tap into Indonesia's growing cosmetics sector while contributing to regional economic development.